Meningkatkan Hasil Belajar Siswa pada Pelajaran IPA dengan Menggunakan Model Kooperatif TGT (Team Games Tournament) di Kelas III UPT SPF SDN 101800 Deli Tua - Nasution, Intan Purnama Sari; Dwi, Dara Fitrah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to improve the learning outcomes of class III students at UPT SPF SDN 101800 Deli Tua in science subjects using the TGT (Team Games Tournament) Cooperative Model in the 2023 – 2024 academic year. This research is Classroom Action Research (PTK) with the research object being There are 30 class III students at UPT SPF SDN 101800 Deli Tua. This research was carried out in two cycles. Based on the results obtained during the classroom action research, it can be explained that student learning achievement during the pre-cycle/pre-test was still low with the percentage of completeness still 9.37% with an average score of 44.79%. In Cycle I, after implementing the TGT (Team Games Tournament) Cooperative Model, the class average increased to 70.7 with a completion percentage of 46.87%. Even though the class average has experienced quite a large increase, the percentage of completion is still low. After Cycle II the class average increased to 85.93 with a completion percentage of 87.50 percent. Based on these results, it can be concluded that implementing the TGT (Team Games Tournament) Cooperative Model can improve learning achievement in class III students at UPT SPF SDN 101800 Deli Tua.